OPTIMALISASI BUDAYA KERJA DALAM RANGKA MENINGKATKAN MUTU PEMBELAJARAN PADA ERA KURIKULUM MERDEKA - Sambella, Mutiara; Suherman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the conditions of work culture in educational institutions in supporting the implementation of the Independent Curriculum, analyze the factors that influence the optimization of work culture, and develop effective strategies to improve the quality of learning through optimizing work culture in the Independent Curriculum era. The method used is a literature study by reviewing various books, journals, and other academic sources that are relevant to this topic. The results of the study indicate that a collaborative, flexible, and professional teacher development-oriented work culture is very important to support the implementation of the Independent Curriculum. Several factors that influence the optimization of work culture in educational institutions include strong leadership, relevant teacher training, and collaboration between all education stakeholders. In addition, to improve shared learning, the strategies that need to be implemented are strengthening a culture of collaboration, developing teacher competencies, and improving leadership that supports changes in learning. By implementing this strategy, it is hoped that a work culture can be created that supports the implementation of the Independent Curriculum and improves the quality of learning in educational institutions.